Karakteristik Empat Aksesi Nilam - Yang Nuryani (Buletin Plasma Nutfah, 2006)
Characterization of four accessions of patchouli was conducted to obtain the information of characteristics to be utilized for future breeding program. The experiment was conducted in three locations namely Ciamis, Cimanggu, and Sukamulya. Four accessions of patchouli namely 0003, 0007, 0012, and 0013 were tested in a randomized block design with five replications, plant spacing of 100 x 50 cm, and 100 plants/plot. The plant were first harvested six month after planting and the 2nd harvested four months after the 1st harvested. The observation were made before the first harvested on morphological characters, production, oil content, and oil quality. The result showed that some of morphological characters such as plant height, accessions of primary and secondary branches, length of primary and secondary branches, length and widh of leaf as weel as numbers of leaves on primary branches on accession of 0012 were higher than that of another three accessions. The highest production of dry terna (13,278 t/ha) and patchouli alcohol content (33,3%) was observed on accession 0012, while the highest oil content (3,2%) on accession 0007. The main morphological characters that can be used to identify those accessions of patchouli was the colour of stem, accessions 0012 was green with slight purple, 0003 and 0007 more purple, and 0012 dark purple. AbstrakKarakteriasi empat aksesi nilam bertujuan untuk mendapatkan informasi mengenai karakter nilam dan pemanfaatannya dalam pemuliaan tanaman di masa yang akan datang. Penelitian dilakukan di tiga lokasi, yaitu Ciamis, Cimanggu, dan Sukamulya. Aksesi 0003, 0007, 0012, dan 0013 dikarakterisasi dalam rancangan acak kelompok dengan lima ulangan, jarak tanam 100 x 50 cm, 100 tanaman per petak. Panen pertama dilakukan pada umur 6 bulan dan panen kedua 4 bulan setelah panen pertama. Pengamatan dilakukan sebelum panen pertama. Parameter yang diamati adalah karakter morfologi, hasil, kadar, dan mutu minyak, serta ketahanan terhadap penyakit. Hasil penelitian menunjukkan tinggi tanaman, jumlah cabang primer/ sekunder, panjang cabang primer/sekunder, panjang dan lebar daun, dan jumlah daun per cabang primer aksesi 0012 lebih tinggi daripada ketiga aksesi lainnya. Produktivitas terna kering (13,278 t/ha) dan kadar patchouli alkohol (33,3%) tertinggi diberikan oleh aksesi 0012, sedangkan kadar minyak tertinggi (3,2%) ditunjukkan oleh aksesi 0007. Karakter morfologi yang membedakan aksesi-aksesi tersebut terutama adalah warna batang tua. Aksesi 0012 memiliki batang tua berwarna hijau dengan sedikit ungu, sementara aksesi 0003 dan aksesi 0007 lebih ungu dan aksesi 0012 paling ungu.